Observing the Diurnal Variations of Ozone‐NOx‐VOC Chemistry Over the U.S. From the Geostationary TEMPO Instrument - Xiaomeng Jin; Yohan Yang; Gonzalo Gonzalez Abad; Caroline Nowlan; Xiong Liu (Geophysical Research Letters, 2025)
Abstract Ground‐level ozone (O3) is an air pollutant formed by the photochemical reactions between oxides of nitrogen (NOx) and volatile organic compounds (VOCs). A key challenge in mitigating O3 pollution is to determine whether the O3 production is NOx‐limited or NOx‐saturated. Using the hourly observations of O3 precursors, formaldehyde (HCHO) and NO2, from the newly launched geostationary Tropospheric Emissions: Monitoring of Pollution (TEMPO), we present the first space‐based observations of diurnal variations of O3‐NOx‐VOC chemistry over the CONUS during 2024 warm season. We integrate a steady‐state model with global simulations to derive the regime thresholds of the HCHO to NO2 ratio (HCHO/NO2), and identify the O3 production regimes using the provisional TEMPO products, which have been validated with limited measurements. We find that O3 production is dominated by NOx‐saturated regime in the morning but NOx‐limited regime in the afternoon over major U.S. O3 nonattainment metropolitan areas.